A química de fluxo contínuo e fotoquímica para a síntese de fármacos - Bernardes, Ana Claudia Bergler (Universidade Federal de São Carlos, 2024)
Drugs are essential for healthcare, and active pharmaceutical ingredients (APIs) are the substances that provide the desired therapeutic effects. The safe, efficient, and robust synthesis of APIs is crucial for the adequate supply of medicines and the developing of new drugs. In this context, synthetic methods to obtain APIs are necessary and require the use of new technologies, such as the combination of photochemistry with continuous flow. Photochemistry uses light to provide energy to molecules, generating transformations that lead to the creation of new compounds. Continuous flow offers greater mass and heat transfer, enhanced safety, reaction efficiency, reduced waste, scalability, and better reproducibility than traditional batch processes. Therefore, in this work, a literature review of the main fundamentals of photochemistry and continuous flow was conducted, followed by the applications of these combined tools for the synthesis of APIs.
Continuous flow chemistry and photochemistry for the synthesis of drugs
Keywords: Fluxo contínuo; Fotoquímica; Síntese; Insumos farmacêuticos ativos; Continuous flow; Photochemistry; Synthesis; Active pharmaceutical ingredients; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA